Therapy for ocular toxoplasmosis (2011)
Purpose: To review current evidence for the treatment of ocular toxoplasmosis (OT). Design: Narrative review and expert recommendations. Methods: Meta-analysis and selected original articles from the medical literature were reviewed critically. Expert recommendations were analyzed. Results: Numerous observational studies suggest a benefit of short-term antimicrobial therapy for toxoplasmic retinochoroiditis in immunocompetent patients, although its efficacy has not been proven in randomized clinical trials. A randomized clinical trial revealed that intermittent trimethoprim/sulfamethoxazole treatment could decrease the rate of recurrence in high-risk patients. Intravitreal injection of clindamycin and dexamethasone was an acceptable alternative to the classic treatment for OT in a randomized clinical trial. Conclusions: Opinions about therapy differ and controversy remains about its type, efficacy, and length. Intravitreal therapy may be promising for OT. A recent description of the presence of parasitemia in patients with active and inactive ocular toxoplasmosis raises new questions that need to be explored.